Writing and research for graphic designers a designer's manual to strategic communication and presentation - Heller, Steven (Beverly, MA Rockport Publishers, 2012)
"For designers, writing and research skills are more necessary than ever before, from the basic business compositions to critical writing. In this competitive climate, designers are routinely called upon to make words about the images and designs they create for clients. Writing about design is not just "trade" writing, but should be accessible to everyone with an interest in design. This book is a complete, introductory guide to various forms of research and writing in design--and how they explain visuals and can be visualized. These pages address communication on various levels and to all audiences:- Designers to Designers- Designers to Clients- Designers to the Design-literate- Designers to the Design-agnosticBeing able to express the issues and concerns of the design practice demands facts, data, and research. With Writing and Research for Graphic Designers, you'll learn how to turn information into a valuable asset-- one of the key talents of the design researcher"-- Provided by publisher.
Includes bibliographical references (pages 163-164) and index.
Keywords: Commercial art -- Marketing; Graphic arts -- Marketing; Business writing; Research; Electronic books